Sub-ablative thermo-stimulation with high-intensity focused ultrasound targeting the nucleus accumbens for severe alcohol use disorder: a feasibility study - Kun-Hong Li; Wei-Chun Chen; Pei-Han Wu; Wei-Chieh Chang (Interdisciplinary Neurosurgery)
Ablative neurosurgical approaches targeting the nucleus accumbens (NAc) have been explored for treating substance use disorders, including alcohol use disorder (AUD). However, the neuropsychologic morbidity paid special consideration to the indications of these surgical techniques. This study presents the outcomes of two male patients, aged 42 and 47 years, diagnosed with severe AUD who underwent magnetic resonance-guided focused ultrasound (MRgFUS) sub-ablative thermo-stimulation targeting the bilateral NAc. At 1-month and 3-month follow-ups, Patient 1 exhibited reductions of 14 % and 54 % in Alcohol Use Disorders Identification Test (AUDIT) scores, 11 % and 56 % in craving visual analogue scale (VAS) scores, and 90 % and 50 % in Beck Depression Inventory-II (BDI-II) scores. Patient 2 demonstrated reductions of 3 % and 27 % in AUDIT scores, 14 % and 43 % in VAS scores, and 44 % and 28 % in BDI-II scores. Single-photon emission computed tomography (SPECT) imaging at 3 months revealed significant changes in regional brain activity comparing with baseline images for both patients. These findings highlight the potential of MRgFUS sub-ablative thermo-stimulation as an alternative minimally invasive intervention for AUD.